2013
DOI: 10.5897/jpbcs2013.0389
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical evaluation of six soybean cultivars using correlation and regression analysis under different irrigation regime conditions

Abstract: Two field experiments were conducted during summer seasons of 2011 and 2012 to study the effect of irrigation regimes at different growth stages on seed, oil and protein yields of soybean cultivars. The interrelationships among seed yield ha-1 and its attributes through simple correlation and stepwise regression analysis were evaluated. The results indicated that the percentages of oil and protein in the seeds were significantly affected by water regimes and caused a decrease in oil percentage and increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
7
15
1
Order By: Relevance
“…The strong linear association found between TNP and Y corroborate previous results (Arshad et al, 2006;Oz et al, 2009;El-Badaway and Mehasen, 2012;Nogueira et al, 2012;Valencia-Ramirez and Moreno, 2012;El-Mohsen et al, 2013;Okonkwo and Idahosa, 2013), suggesting that selection based on the number of pods per plant contributes to the selection of genotypes with high grain yields.…”
Section: (Equation 9)supporting
confidence: 80%
See 1 more Smart Citation
“…The strong linear association found between TNP and Y corroborate previous results (Arshad et al, 2006;Oz et al, 2009;El-Badaway and Mehasen, 2012;Nogueira et al, 2012;Valencia-Ramirez and Moreno, 2012;El-Mohsen et al, 2013;Okonkwo and Idahosa, 2013), suggesting that selection based on the number of pods per plant contributes to the selection of genotypes with high grain yields.…”
Section: (Equation 9)supporting
confidence: 80%
“…This result disagrees with those obtained by El-Mohsen et al (2013), who reported significant positive correlations between HPM and TNP with six soybean cultivars over two consecutive seasons when evaluating the effects of irrigation on different stages of seed development. NDB was significantly and positively phenotypically correlated with NDM, NP2G, and TNP, with genotypic correlations greater than 0.63 (Table 2).…”
Section: (Equation 9)contrasting
confidence: 56%
“…Genotypic correlation coefficient values were greater for most of the characters than their corresponding phenotypic correlation coefficient values, indicating inherent association of the characters. Positive significant associations were obtained between grain yield and plant height because these tall lines generally excelled in their capacity to support seed growth by stem reserve mobilization [23]. Therefore, selection for tall plants tends to increase grain yield per plant.…”
Section: Discussionmentioning
confidence: 85%
“…In the regression model, it was shown that plant height, seed-filling period and total dry matter affect the yield of soybean. El-Mohsen et al (2013) showed simple linear regression analysis of important relationships of irrigation regimes and seed, oil and protein yield. The obtained models were Y=2976-258.9X (R 2 =0.62), Y=568.1-50.55X (R 2 =0.54), Y=1187-96.96X (R 2 =0.64).…”
Section: Discussionmentioning
confidence: 99%